Personnel perceptions of a positive practice environment in public nursing education institutions in South Africa: A descriptive qualitative study - Anna F. Bence; Hester C. Klopper; Siedine K. Coetzee (Elsevier, 2024)
Background: While much is known about aspects of the practice environment and its influence on staff outcomes and quality of education, less is known about creating positive practice environments in public nursing education institutions, especially in developing countries. Aim: To describe the perceptions of the personnel of a public nursing education institution identified as having the most positive practice environment and nurse educator outcomes. Design: A qualitative descriptive research design was used. Methods: All-inclusive voluntary sampling was applied at one public nursing education institution in the Gauteng Province with the principal, vice-principal, heads of departments (N = 11; n = 6), nurse educators (N = 93; n = 17), and administrative staff (N = 42; n = 11). Semi-structured individual and focus group interviews were conducted and inductive thematic analysis was used. Data was collected from November 2019 until March 2020. Results: Personnel indicated interpersonal relationships, effective communication and enhancing team dynamics as the main theme of the study, with seven specific sub-themes as raised by managers, nurse educators and administrative staff. Conclusion: Interpersonal relationships, communication and enhancing team dynamics is the main drive for a positive practice environment. The most significant responsibility in creating such an environment is the managers' ability to lead and support personnel. In addition to intentionally fostering collegial and collaborative relationships, managers need to be approachable. In addition to upholding fundamental human rights values and fostering active participation in decision-making, managers should exercise sensitive leadership. and encourage staff wellness support measures. Twitter abstract: Interpersonal relationships, effective communication and enhancing team dynamics are the most crucial tactics for promoting positive practice environments at public nursing education institutions in a province of South Africa.